Are physical activity, sedentary behaviors and sleep duration associated with body mass index-for-age and health-related quality of life among high school boys and girls? - Jalali-Farahani, Sara; Amiri, Parisa; Yit, Siew Chin (BioMedical Central, 2016)
Background: Previous studies reported lower health-related quality of life (HRQOL) scores in overweight and obese adolescents compared to their normal weight counterparts; however, few studies investigated the association between obesity-related behaviors including physical activity and sedentary behaviors and HRQOL in adolescents. This study aimed at investigating the relationship between physical activity, sedentary behaviors, sleep duration and body mass index-for-age (BMI-for-age) and HRQOL among high school Tehranian students. Methods: A total of 465 high school students (48.8 % girls) were recruited from three different socio-economic zones in Tehran. The BMI-for-age was determined and physical activity and HRQOL were assessed using validated questionnaires including Quantification de l’Activite Physique en Altitude Chez les Enfants (QAPACE) and Pediatric Quality of Life Inventory (PedsQL) respectively. Results: Over one third of students (38.5 %) were either overweight or obese. The means of all self- and parent-reported HRQOL scores were significantly lower in girls, compared to boys, except for the parent-reported social functioning subscale. Mean hours of daily sleeping were significantly higher in girls, compared to boys (8.16 ± 1.27 vs. 7.73 ± 1.22 respectively; p < 0.05). Both girls and boys spent more time on sedentary activities than engaging in sport activities. During school and vacation periods, boys had significantly higher daily energy expenditure (DEE) compared to girls (p < 0.05). Only DEE during school period had a significant inverse correlation with BMI-for-age in boys but not girls (r = −0.14, p < 0.05). In addition, self-reported HRQOL scores were significantly associated with weekly hours adolescents spent on videogames/internet, listening to music and reading, watching TV, sports as well as DEE through sex-specific patterns. However according to parents’ perspective only weekly hours spent on listening to music and readings and sport activities were significantly associated with their children HRQOL scores. Conclusion: In summary, time spent on physical and sedentary activities were not associated with BMI-for-age, although both of these were associated with the HRQOL of high school students. The potential role of sedentary activities and physical activity should be considered in future interventions aimed at improving HRQOL in adolescents.